MXenes: advances in the synthesis and application in supercapacitors and batteries - Wasnik, Kundan; Pawar, Meenakshi D.; Raphael, Leya Rose; Pullanchiyodan, Abhilash; Shelke, V. Manjusha; Raghavan, Prasanth (Journal of Materials Research, 2022)
MXenes, the newest family member of the two-dimensional materials have been widely investigated for different applications, particularly in the energy storage realm. With regard to this, MXene precursors have attained widespread attention for the application in electrochemical energy storage devices especially supercapacitors and batteries. This review has comprehensively studied various synthesis strategies adopted for MXenes including the top-down and bottom-up approaches. The shift to renewable energy alternatives have focused on the electrochemical choices such as supercapacitors and batteries, the most common and relevant ones. Thus the application of MXenes and its composite in supercapacitors as electrodes have been analyzed along with its detailed mechanism and electrochemical performance. Several battery chemistries including lithium-ion, sodium-ion and other battery systems utilizing MXenes have also been discussed here. Thus the existing strategies, advancements, and drawbacks regarding the inclusivity of MXenes in the electrochemical energy systems of supercapacitors and batteries are reviewed in this article.